Postawa chrześcijanina wobec śmierci w świetle "De mortalitate" św. Cypriana z Kartaginy - Czyżewski, Bogdan Stanisław (Vox Patrum, 2024)
In his small work entitled De mortalitate, written in the form of a letter, St. Cyprian of Carthage includes a beautiful teaching on suffering, dying and death. The bishop comforts those who have been affected by the present plague and are facing their departure from this world. He teaches them to view death from the perspective of a believer and to see it as a positive, although painful, phenomenon. Since death must be experienced in an eschatological spirit, as an encounter with the Risen Christ and with all those who preceded us on the pilgrimage to immortality. According to the Bishop of Carthage, death teaches man right attitudes, such as patience, courage, and acceptance of the will of God. Moreover, Cyprian shows specific benefits that death brings to Christians. He calls it a journey to a better, eternal life. Thus those who relate their earthly lives to Christ should not fear death. The purpose of this study is therefore to study the statements of St. Cyprian contained in De mortalitate on the subject of death. It is not only about assessing it, but primarily about reading the practical instructions addressed to Christians on how they should behave in the face of this inevitable reality, especially during the current plague.